Women in the Synoptic Gospels: Seen but not Heard? - Dewey, Joanna (Biblical theology bulletin, 1997)
This article presents a quantitative analysis of the literary portrayal of male and female minor characters interacting with Jesus in the Synoptic Gospels. It asks, “Are the women characters presented with as much mimetic vividness as the male characters?” After illustrating the method by a comparison of the depiction of Mary in Matthew's and Luke's infancy narratives, I analyze the healings, and then discussother stories involving minor characters. All three Gospels are androcentric in their narrative portrayal, describing male characters with more detail than female characters, portraying males speaking to Jesus and being addressed by Jesus more often than female characters. The other stories present an interesting picture: the woman acts, and then others, usually men, discuss her behavior. The women are seen but not heard.